Superconductivity suppression at twin boundaries and longitudinal and transversal transport anisotropy in oxygen deficient YBa₂Cu₃O₇₋ₓ single crystals - Vovk, R.V.; Obolenskii, M.A.; Zavgorodniy, A.A.; Bondarenko, A.V.; Goulatis, I.L.; Chebotaev, N.N. (Functional Materials, 2007)
The temperature dependences of the conductivity along and across the basis plane have been measured in YBa₂Cu₃O₇₋ₓ single crystals with different oxygen non-stoichiometry. In the oxygen-deficit samples, an inhomogeneous oxygen distribution within the crystal bulk is found, that results in the formation of phases with different critical of superconducting transition temperatures. The accordance of the experimental results with the predictions of different theoretical models has been considered. It has been revealed that the anisotropy of the normal resistivity pc/pab(T) is described well using the universal "law of 1/2", for thermal activation of the hopping conductivity.